The Impact Of Technological, Organizational And Environmental Factors Of Erp Diffusion Among Smes In Saudi Arabia: Perceived Values As The Mediator - S Alzughaibi, Saad Mohammed (2022)
Enterprise resource planning ERP refers to the integrated central systems that businesses use to store and process information, facilitate its exchange between different departments, and assist in effectively administering procedures. The past research theories show that ERP systems bring a variety of technical, operational, and strategic benefits, such as sharing information, reducing costs, streamlining business processes, productivity, efficiency, customer service, and supply chain communication. It was shown that ERP systems had provided similar benefits to small and medium-sized enterprises (SMEs) as they had too large enterprises (LEs). However, SMEs’ contributions to the country’s economy and capital market are limited due to a lack of ERP deployment and an understanding of ERP’s benefits. Although there is no agreement on the number and nomenclature of ERP system diffusion stages, the majority of researchers identified three: evaluation, adoption, and routinization. Studying these stages is of utter importance for stakeholders to take appropriate decisions, but there is little research on these stages. This approach fails to demonstrate how technology is fully integrated into an organisation.